Avaliação da durabilidade do concreto utilizado em postes em São Luís - Santos, Vito Assis Alencar dos (2016)
Reinforced concrete structures built in coastal areas, such as electricity distribution poles, are constantly attacked by aggressive environmental agents. Rebar corrosion mechanism is a specific manifestation of electrochemical corrosion in an aqueous medium, thus the mechanism of corrosion of steel in concrete develops only in the presence of water or environment with high relative humidity (R.H.>60%). Chloride is known as one of the most aggressive environmental agents, causing rebar corrosion and consequent degradation of the concrete. Chlorides can reach the steel reinforcement through the pores network present in the concrete, if the device is close to marine atmosphere. The chloride content increases with time, and can attack the entire surface of the rebar, and may result in severe and dangerous corrosion velocity. Corrosion results in a decrease in rebar section and cracking of the concrete in parallel direction. The cracks occur because of corrosion products occupy more space than the original steel. In São Luis, concrete poles located on the coastal area has presented different types of pathology, mostly linked to performance of the chlorine ions. As a consequence, the life of these parts has reduced dramatically, generating maintenance costs. Therefore, this study intended to develop alternatives aimed at increasing the durability of reinforced concrete poles, by reducing the transfer of chlorides in their concrete cover, through variations in trace and concrete chemical composition, evaluating the influence of these parameters on its mechanical resistance. Therefore, many specimens were shaped with different compositions, using Type CPII E-32 Portland cement (compound slag) with water / cement ratio ranging between 0.4 and 0.5. Concrete mixtures containing silica fume (in order to reduce the capillary) and red mud additions (in order to protect the equipment by reducing the free chloride content) were also tested. Durability assessment of concrete was based on the results of its physical and mechanical characterization, on the electrical resistivity evaluation of concrete and rebar corrosion potential. Results show that silica fume and red mud addition reduces porosity and water absorption of concrete samples, as well increases mechanical strength, when compared to currently used concrete for poles manufacturing in São Luis. Additionally, it revealed a drastic reduction in rebar corrosivity when covered by concrete with these additions, tripling the life time of poles.